PENGARUH PROFITABILITAS, LEVERAGE, UKURAN PERUSAHAAN, OPINI AUDITOR, DAN REPUTASI AUDITOR TERHADAP AUDIT DELAY TAHUN 2022-2024 - Yonathan, Yessica; Paramitha, Melvie (J-MACC : journal of management and accounting, 2026)
Companies listed on the Indonesia Stock Exchange are required to report quarterly and annual financial reports, as well as sustainability reports. For public companies, the deadline for submitting annual reports is no later than the end of the third month of the following year, together with the sustainability report. Owners of publicly listed companies will continue to maintain their best reputation in order to maintain the trust of investors and the public. Therefore, the author conducted this study with the aim of examining whether there is an influence of Profitability, Leverage, Company Size, Auditor Opinion, and Auditor Reputation on Audit Delay in Transportation and Logistics Sub-Sector Companies Listed on the Indonesia Stock Exchange (IDX) from 2022 to 2024. This study uses a quantitative method with secondary data from 102 samples of companies in the Transportation and Logistics Sub-Sector. The sample selection uses a purposive sampling method. The results of this study using SPSS 23 show that the Profitability variable has an effect on Audit Delay, while Leverage, Company Size, Auditor Opinion, and Auditor Reputation have no effect on Audit Delay.